Shipwreck on the Pirate Islands - Stilton, Geronimo; Stracchino, Johnny; Fontina, Mary; Edizioni Piemme (New York : Scholastic, 2005)
Geronimo goes to a desert island in search of haunted pirate treasure
3
007-010
Keywords: Stilton, Geronimo -- Fiction; Mice -- Juvenile fiction; Treasure troves -- Juvenile fiction; Islands -- Juvenile fiction; Mice -- Fiction; Buried treasure -- Fiction; Islands -- Fiction; Fiction